Revisiting the Southeast Asian House: An Outlier’s Perspective - Zialcita, Fernando N (Archīum Ateneo, 2021)
Overviews of Southeast Asian houses often overlook Hispanised Philippine houses. This chapter suggests that we need a perspective that will include not only such houses but also vernacular houses using brick or stone in northern Vietnam and South Sumatra. The argument is framed around a number of key points. First, because Southeast Asia is a recent construct dating back only to 1944–1945, defining frameworks should be flexible. Second, to pursue the Austric-Tai hypothesis about the underlying unity of the three language families—Austronesian, Austroasiatic and Tai-Kadai—research in nonlinguistic domains like architecture is needed. Third, we should be wary of the lingering tendency to prioritise Indianisation as the key integrating motif and conversely to exclude Chinese and especially Western influences as an excrescence. Fourth, in the urban centres new influences may have reshaped indigenous traditions, but these indigenous traditions in turn localised the foreign. And finally, the localisation of once-foreign traditions could be analysed in the future on the basis of materiality, functionality and symbolism. For instance, the eighteenth- and nineteenth-century Philippine house and South Sumatra’s rumah gedung seem similar in being constructed of wood above and stone below. What would the differences be in construction methods, function and symbolism?